Mechanism of abnormal specification of spermatogonial stem cells after Rb1 knockout in mitotic-arrested prospermatogonia - CHEN Xinling; CHEN Xinling; LONG Yixuan; DU Guihua; DU Guihua (陆军军医大学学报)
Objective‍　‍To investigate the underlying mechanism of abnormal specification of spermatogonial stem cells （SSCs） in male mice following Rb1 conditional knockout in mitotic-arrested prospermatogonia. Methods‍　‍① R language was used to analyze the single-cell RNA sequencing （scRNA-seq） data of prospermatogonia derived from postnatal day 0.5 （P0.5） male mice through the gene expression omnibus （GEO） public database （accession number： GSE124904）. ② Mitoti-arrested prospermatogonia Rb1 conditional knockout （cKO） mice as well as Rb1 cKO mice with Id4-gfp transgene were generated using Vasa-Cre mice crossed with Rb1flox/flox or Id4-gfpTg；Rb1flox/flox mice. PCR was employed to detect the deletion of Rb1 in order to distinguish the control and cKO male mice. The testes of male mice （n=3~8） within a few days after birth were collected. After that， flow cytometry was applied to divide the ID4-GFP cells into 3 communities based on the GFP fluorescence intensity， and then detect the number of cells and cell cycle in each community. ③ Germ cell proliferation （Ki67 positive， Ki67+）， SSCs specification （FOXO1 nuclear transition）， and germ cell differentiation （STRA8+） were detected with immunofluorescence staining. ④ TUNEL staining was utilized to detect cell apoptosis. Results‍　‍① The results of scRNA-seq showed that in the two set clusters of prospermatogonia， the prospermatogonia that further specifies to generate SSCs had enriched genes that are associated with cell proliferation. ② Germ cell proliferation assay indicated that the average ratio of Ki67+ germ cells in the testicular cross-section of the cKO mice was significantly higher than that of the control mice at P2.5 ［（46.10±6.21）% vs （11.22±3.27）%， P<0.01］. ③ Flow cytometry revealed that， among the brightest community of ID4-GFP cells， the percentage of the cells at S phase was obviously higher in the testicular cells derived from the cKO mice when compared to the control mice at P2.5 ［（12.05±1.22）% vs （5.05±1.46）%， P<0.05］.④ TUNEL staining displayed that cell apoptosis was detected in the testicular cross-section of cKO mice rather than that of the control mice. ⑤ The results of SSCs specification exploration showed that statistical difference was observed in the percentage of cytoplasmic FOXO1 in the testicular cross-section between the control and cKO mice ［（20.57±2.15）% vs （45.08±2.45）%，P<0.01］. Conclusion‍　‍Rb1 knockout in mitotic-arrested prospermatogonia disrupts their postnatal cell cycle re-enter and induces cell apoptosis， which further results in abnormal SSC specification.